PRICE INTEGRATION ANALYSIS AMONG RUBBER MARKETS OF THAILAND - จตุพร เฉลิมพล; สุขประเสริฐ พัฒนา (RMUTT Global Business and Economics Review, 2016)
The purpose of this study is to analyze the impacts of price transmission among rubber markets of Thailand, namely, farmgate, wholesale, export and world market prices. The monthly time series are utilized covering the period of January 2001 to December 2015. The econometric techniques are employed to satisfy the purpose including (1) the ADF unit root for testing stationarity, (2) the Johansen cointegration for testing long-run equilibrium relationship and (3) the Granger causality for analyzing price integration. The empirical findings can detect the impacts of price integration among the markets of Thailand. There are from wholesale, export and world market prices running to farmgate price as well as from wholesale and world market prices running to export price.